1999
DOI: 10.1128/mcb.19.1.12
|View full text |Cite
|
Sign up to set email alerts
|

p53-Mediated Regulation of Proliferating Cell Nuclear Antigen Expression in Cells Exposed to Ionizing Radiation

Abstract: The proliferating cell nuclear antigen (PCNA) is a highly conserved cellular protein that functions both in DNA replication and in DNA repair. Exposure of a rat embryo fibroblast cell line (CREF cells) to gamma radiation induced simultaneous expression of PCNA with the p53 tumor suppressor protein and the cyclin-dependent kinase inhibitor p21(WAF1/Cip1). PCNA mRNA levels transiently increased in serum-starved cells exposed to ionizing radiation, an observation suggesting that the radiation-associated increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 106 publications
(143 reference statements)
6
56
0
Order By: Relevance
“…Instead, the genes (p48, XPC, gadd45, PCNA) have roles in nucleotide excision repair, a pathway conventionally associated with UVinduced damage (19)(20)(21)(22). We confirmed the induction of these genes by Northern blot (23)(24)(25). Fornace et al reported defective removal of base damage induced by IR in xeroderma pigmentosum cells (26).…”
Section: Resultssupporting
confidence: 72%
“…Instead, the genes (p48, XPC, gadd45, PCNA) have roles in nucleotide excision repair, a pathway conventionally associated with UVinduced damage (19)(20)(21)(22). We confirmed the induction of these genes by Northern blot (23)(24)(25). Fornace et al reported defective removal of base damage induced by IR in xeroderma pigmentosum cells (26).…”
Section: Resultssupporting
confidence: 72%
“…Most of these genes can be sorted according to their potential involvement in the SIPS phenotype. First, genes involved in growth arrest are overexpressed: insulin-like growth factor binding protein 3 (IGF-BP3) (Buckbinder et al, 1995), IGF-BP5 (Caroni and Schneider, 1994), p21 WAF-1 (Sherr and Roberts, 1999), MAX (Ayer et al, 1993) and proliferating cell nuclear antigen (PCNA) (Xu and Morris, 1999). Cyclin D1 is overexpressed as previously found in replicative senescence (Fukami et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The precocity of this induction after irradiation and the parallel with WAF1 mRNA induction indicated that the promoter of PCNA could be transactivated by p53, but probably a threshold of DNA damages should be achieved within the cells. In this respect, Xu and Morris (1999) found that, 1 h after gamma irradiation (12 Gy) of rat embryo ®broblasts, a p53 dependent induction of PCNA mRNA and protein took place, and on human diploid ®broblasts similar induction was seen after UV irradiation (Zeng et al, 1994). Inversely, by Western blot analysing of irradiated human lymphoblastoid cell lines, Wenz et al (1998) found considerable changes in intranuclear distribution and complex formation of PCNA which are not associated with change in PCNA protein level.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA belongs to a multi-protein complex implicating DNAligase-I (Lig-1), and is involved in joining of Okasaki fragments during replication, and in NER or BER repair process (Tomkinson and Mackey, 1998). The interaction between Waf1 and PCNA blocks replication and/or repair function of PCNA (Li et al, 1994;Waga et al, 1994), but PCNA itself could be directly regulated by p53 (Xu and Morris, 1999).…”
Section: Introductionmentioning
confidence: 99%